KONTRUKSI SOSIAL MASYARAKAT MANDAR TERHADAP PASSAU’ WAI DI DAERAH ALIRAN SUNGAI (DAS) MANDAR - Nur Fitriani Maskur (Bajang Institute, 2025)
Mandar defined as water, thus Mandarnese society is a community that closely related to the water, which is formed from seven kingdoms upstream and seven kingdoms downstream of the river